Respuesta :
Greetings!
Answer:
B)
Step-by-step explanation:
Y intercept:
Simply substitute all the x values with 0:
When x = 0:
3(0) - 2y = 18
Move the - 2y over to the other side making it a +2y:
0 = 18 + 2y
Move the +18 over to the other side making it a -18:
-18 = 2y
Divide both sides by 2:
[tex]\frac{-18}{2} = \frac{2y}{2}[/tex]
-9 = y
So y intercept is:
(0 , -9)
X - intercept:
Simply substitute all the Y's with 0:
3x - 3(0) = 18
3x = 18
Divide both sides by 3:
[tex]\frac{3x}{3} = \frac{18}{3}[/tex]
x = 6
So the X intercept is:
(6 , 0)
This means that your guess of B is correct.
Hope this helps!
Answer:
B) → x-intercept = (6, 0) and y-intercept = (0, -9.)
First, we'll work with y, where we'll substitute x by 0:
3(0) - 2y = 18
0 - 2y = 18
-2y = 18 + 0
-2y = 18
y = 18 / -2
y = -9 → y-intercept = 0, -9 ←
↑ Many people wonder where the "0" comes from, and it's just the place where the x-intercept value would be placed in a system of equations.
Second, we'll work with x, following the same method as before, this time, substituting y by 0:
3x - 2(0) = 18
3x - 0 = 18
3x = 18 + 0
3x = 18
x = 18 / 3
x = 6 → x-intercept = 6, 0 ←
↑ Same here. The "0" is just the place where the y-intercept value would be, if we were working with a system of equations.
Hope it helped
BioTeacher101